Consequences of removing cheap, super-strength beer and cider: a qualitative study of a UK local alcohol availability intervention. Issue 9 (29th September 2016) - McGill, Elizabeth; Marks, Dalya; Sumpter, Colin; Egan, Matt
Abstract : Objectives: Increasingly, English local authorities have encouraged the implementation of an intervention called 'Reducing the Strength' (RtS) whereby off-licences voluntarily stop selling inexpensive 'super-strength' (≥6.5% alcohol by volume (ABV)) beers and ciders. We conceptualised RtS as an event within a complex system in order to identify pathways by which the intervention may lead to intended and unintended consequences. Design: A qualitative study including a focus group and semistructured interviews. Setting: An inner-London local authority characterised by a high degree of residential mobility, high levels of social inequality and a large homeless population. Intervention piloted in three areas known for street drinking with a high alcohol outlet density. Participants: Alcohol service professionals, homeless hostel employees, street-based services managers and hostel dwelling homeless alcohol consumers (n=30). Results: Participants describe a range of potential substitution behaviours to circumvent alcohol availability restrictions including consuming different drinks, finding alternative shops, using drugs or committing crimes to purchase more expensive drinks. Service providers suggested the intervention delivered in this local authority missed opportunities to encourage engagement between the council, alcohol services, homeless hostels and off-licence stores. Some participants believed small-scale interventions such as RtS may facilitate new forms of engagement between public and private sector interests and contribute to long-term cultural changes around drinking, although they may also entrench the view that 'problem drinking' only occurs in certain population groups. Conclusions: RtS may have limited individual-level health impacts if the target populations remain willing and able to consume alternative means of intoxication as a substitute for super-strength products. However, RtS may also lead to wider system changes not directly related to the consumption of super-strengths and their assumed harms.